Análise e otimização da rede de distribuição de energia utilizando conceitos de redes inteligentes - Caetano Neto, João (2021)
The main objective of this work is to develop a methodology for analyzing the quality of the voltage level in the distribution power grid to identify and re-duce the violations of voltage limits through the proposition of optimal points for the allocation of photovoltaic distributed generation. The methodology uses the geographic location of the power grid and its consumers to perform the grouping and classification in spatial grids of 100×100 m using the average annual consumption profile. The generated profiles, including the grid infor-mation, are sent to the photovoltaic distributed generation allocation algo-rithm, which, using an optimization process, identifies the geographic location, the required installed capacity, and the minimum number of photovoltaic gen-eration units that must be inserted to minimize the violations of voltage limits, respecting the necessary restrictions. The entire proposal is applied in a real feeder with thousands of bars, whose model is validated with measurements carried out in the field. Different violations of voltage limits scenarios are used to validate the methodology, obtaining grids with better voltage quality after the optimized allocation of photovoltaic distributed generation. The proposal presents itself as a new tool in the work of adapting the voltage of the distri-bution power grid using photovoltaic distributed generation.